PENGARUH STRUKTUR PENGENDALIAN INTERN DAN SISTEM PENGENDALIAN INTERN TERHADAP EFEKTIVITAS PENYALURAN KREDIT PADA PERBANKAN SYARIAH DI KOTA PALEMBANG - Welly Welly (Universitas Indo Global Mandiri)
Banking is a financial institution that plays an important role in the economic growth rate, where one of His ministry is lending or credit to the public. Through this service the community greatly helped in continuing the business that mostly have limited capital. In the provision and distribution of bank credit have a standard operating procedure (SOP) which aims to provide uniformity and ease of operation and administration, so as to avoid things that are not desirable. Internal control structure is composed of five elements, namely the control environment, risk assessment, control activities, information and communication and monitoring has a role in terms of lending. Likewise with the internal control system which includes organizational structure, authorization system, practice a healthy and capable and competent employees. So that the formulation of the issues raised in this study there are two: first, how the influence along the internal control structure and system pengendalin intern on the effectiveness of lending in Islamic banking in the city of Palembang, the second how the influence of the partial internal control structure and system pengendalin intern on the effectiveness of lending in the banking sharia in the city of Palembang. The purpose of this study is to determine the effect of the internal control structure and system of the effectiveness of internal pengendalin lending collectively and partially (the case study on Islamic banking in the city of Palembang). Type of associative research, using primary and secondary data. The data collection techniques using questionnaires, interviews and documentation. Methods of data analysis is a quantitative and qualitative analysis by using SPSS. The results showed that the internal control structure and internal control system effecting simultaneously on the effectiveness of lending. The magnitude of the effect of the internal control structure and internal control system of the effectiveness of the loan portfolio by 20%. Internal control system does not affect the effectiveness of the loan portfolio, while the internal control structure significantly influence the effectiveness of the loan portfolio